2017
DOI: 10.1093/jamia/ocx060
|View full text |Cite
|
Sign up to set email alerts
|

Participatory design of probability-based decision support tools for in-hospital nurses

Abstract: Participatory design served as a valuable method in taking the first step toward developing PB-CDS tools for nurses. This information about preferred design elements of tools that support, rather than interrupt, nurses' cognitive workflows can benefit future studies in this field as well as nurses' practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 40 publications
2
38
0
Order By: Relevance
“…In particular, access to raw patient data (e.g., laboratory values, vital signs, interventions) was seen as useful for assessing the clinical credibility and utility of predictions and explanations. This finding is consistent with results from studies by Wang et al [15] and Jeffery et al, [42] both of whom also found that providers utilized raw patient data when working with probability-based decision support systems to verify predictions and to integrate them with their clinical knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, access to raw patient data (e.g., laboratory values, vital signs, interventions) was seen as useful for assessing the clinical credibility and utility of predictions and explanations. This finding is consistent with results from studies by Wang et al [15] and Jeffery et al, [42] both of whom also found that providers utilized raw patient data when working with probability-based decision support systems to verify predictions and to integrate them with their clinical knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, any restrictions in the coding space will necessitate, at least for the purposes of direct care, efficient systems to capture annotations (unstructured notes). This importance of narrative description for enabling more nuanced decision making is highlighted across several included studies; the ability to 'paint a picture' over time [56] of a patient's care trajectory is an important dimension that is currently not consistently captured in contemporary EHR systems. Agreement on the standards to be used, and the data to be collected at the point of care, is a precondition for ensuring effective decision support, and the reuse of data for quality of care indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Agreement on the standards to be used, and the data to be collected at the point of care, is a precondition for ensuring effective decision support, and the reuse of data for quality of care indicators. Further research to focus on the types of cognitive support health professionals require [57], including the use of participatory design approaches [56] will help to ensure systems are fully integrated with nurse workflow. Identifying what decisions need to be supported and for whom (based on user characteristics such as expertise), may also ensure better tailoring of CDS interventions (moving away from a proliferation of alerts) and a tighter focus on safety and quality-critical issues (such as prescribing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Please entitle each table with case/subject number Figure 1 is a screen shot of the dashboard prototype, we have revised this and hope it is and make sure the numbers mentioned in Results are consistent with the ones in Tables. For example, in Satisfying, dashboard information (mean 7.8; SD 1.1) is not consistent with the result in Table 2 (6), and express a need for support in synthesizing the available information to paint a 'picture of the patient' over time (7). In an effort to help clinicians integrate data regarding diagnoses and treatment interventions for patients across time, a number of studies have developed techniques for visual display of patient data both at the individual and group level (8)(9)(10)(11).…”
mentioning
confidence: 89%